Risk and Outcome of Venous and Arterial Thrombosis in Patients With Cirrhosis: A Danish Nation‐wide Cohort Study. Issue 5 (9th September 2021) - Jepsen, Peter; Tapper, Elliot B.; Deleuran, Thomas; Kazankov, Konstantin; Askgaard, Gro; Sørensen, Henrik Toft; Vilstrup, Hendrik; West, Joe
Abstract : Background and Aims: Cirrhosis affects hemostasis, but its effects across the spectrum of thromboses remain poorly understood. We examined risks and outcomes of venous and arterial thrombosis. Approach and Results: We used nation‐wide Danish health care registries to identify outpatients with cirrhosis and a sex‐ and age‐matched comparison cohort without cirrhosis from the general population. Patients with cirrhosis and comparators were followed until they had a venous thromboembolism (VTE), acute myocardial infarction (AMI), or ischemic stroke (IS) or died. We computed absolute risks and HRs of thrombosis and compared outcomes after thrombosis. We included 5, 854 patients with cirrhosis (median Model for End‐Stage Liver Disease score, 9; interquartile range, 7‐13), and their risk of any of the thrombotic events was 0.8% after 1 year and 6.3% after 10 years. They were more likely than the 23, 870 matched comparators to have a VTE (adjusted hazard ratio [aHR], 2.0; 95% CI, 1.5‐2.6) or IS (aHR, 1.7; 95% CI, 1.3‐2.3), but not AMI (aHR, 0.7; 95% CI, 0.5‐0.9). Among patients with cirrhosis, decompensation increased the risk of AMI, but not the other thromboses. Following thrombosis, patients with cirrhosis had higher 90‐day mortality than comparators (after VTE: 17% vs. 7%; after AMI: 27% vs. 5%; after IS: 10% vs. 7%) and were less likely to receive antithrombotic treatment. Conclusions: Patients with cirrhosis had an increased risk of VTE and IS, but not AMI. Among patients with cirrhosis, decompensation increased the risk of AMI, exclusively. Mortality after thrombosis was higher in patients with cirrhosis than in other patients. These findings are relevant for decisions about antithrombotic prophylaxis in patients with cirrhosis.